A co-production of sugars, lignosulfonates, cellulose, and cellulose nanocrystals from ball-milled woods. (August 2017) - Du, Lanxing; Wang, Jinwu; Zhang, Yang; Qi, Chusheng; Wolcott, Michael P.; Yu, Zhiming
Graphical abstract: Highlights: Micronized wood facilitates the co-production procedures. The mass balance points out the potential of cellulose and lignin recovery. Holistically, the study demonstrated the concept of co-production would be realizable. Abstract: This study demonstrated the technical potential for the large-scale co-production of sugars, lignosulfonates, cellulose, and cellulose nanocrystals. Ball-milled woods with two particle sizes were prepared by ball milling for 80 min or 120 min (BMW80, BMW120 ) and then enzymatically hydrolyzed. 78.3% cellulose conversion of BMW120 was achieved, which was three times as high as the conversion of BMW80 . The hydrolyzed residues (HRs) were neutrally sulfonated cooking. 57.72 g/L and 88.16 g/L lignosulfonate concentration, respectively, were harvested from HR80 and HR120, and 42.6 ± 0.5% lignin were removed. The subsequent solid residuals were purified to produce cellulose and then this material was acid-hydrolyzed to produce cellulose nanocrystals. The BMW120 maintained smaller particle size and aspect ratio during each step of during the multiple processes, while the average aspect ratio of its cellulose nanocrystals was larger. The crystallinity of both materials increased with each step of wet processing, reaching to 74% for the cellulose.